El papel de la nutrición de peces en la mejoría de la salud humana y la seguridad mundial. The role of fish nutrition in improving human health and global good security - Tacon, Albert G.J. (Avances en Nutrición Acuicola, 2022)
Malnutrition represents the world’s greatest preventable health challenge, including both undernutrition and overnutrition. The role play by fish and seafood in global food supply and within the Americas is discussed, with aquatic food products offering a much healthier alternative to farmed terrestrial meat products. The paper highlights the important role played by fish nutrition in the formulation of fish and shrimp feeds, and in particular for the nutritional enhancement of farmed fish products through dietary fortification with essential nutrients and improved health attributes.